Henriqueta Lisboa e Maurice Blanchot: o ato criativo e a estranha aproximação com a morte - Araújo, Márcia de Mesquita (2019)
This research consists fundamentally in a critical study of a selection of poems by Henriqueta Lisboa, from her Complete Works (1985), in a possible dialogue with Blanchot’s thought about the creative act and it’s strange approximation to death, marking, thus, a neighborhood or a distinction between them. While studying the poems, we have realized some affinity between them and the theme of death, especially in the books Prisioneira da noite [Prisoner of the night] (1939), A face lívida [The livid face] (1945) e Flor da Morte [Flower of death] (1949), mainly the last two ones. With the exercise of writing, which Henriqueta calls her profession of faith, the poet from Minas Gerais transmuted increasingly her style, in which the theme of death was always present. The french philosopher Maurice Blanchot experiences, delineates a singular conception of literary text. His thought navigates towards the improbable, the unthinkable, the (im)possible of everything engendered in the threshold of writing, as an investment traced in a vigorous spelling, distilled in lines that irradiate, dragging us to the edges of a lugubrious place, in a space where one of the most dear images is that of death. In effect, around L’espace Littéraire (1955), starting point for the reflexive dialogues we intend to develop, questions that scintilates among thought, language, life and death arise here; but not our world’s death, the common sense’s death, instead, it’s a death that does not die, that is dying forever. Therefore, the tangle of theoretical and literary texts make them approach each other by means of reflections on the process of literary writing, in which one can see conceptions of the creative act symbolized by death in both mentioned authors. We shall develop our research in three paths: “Dear Henriqueta”, in which the letters studied reveal dialogues on literary questions and poetry conceptions discussed in the epistolary space; “Poetry sees the war”, in which we make a reflection on the period of the Second World War and how poetry establishes a dialogue with this context of horror; finally, “The strange approximation to death”, in which we go more effectively through the theme of death in Lisboa’s poetry. In these paths, through which only writing guides us, we have raised issues concerning art, literature and literary criticism. The theoretical basis of the research includes names, beyond the ones of Henriqueta and Blanchot, such as Giorgio Agamben, Martin Heidegger, Gilles Deleuze & Felix Guattari, Mallarmé, Octavio Paz, among others. And writing goes on… always increased with possibilities, pluralities.